Early detection of cerebral palsy in infants and young children using DDST II - Kumar, Pankaj; Yasmin, Erum; Fazal, Dr. Kamran (Student’s Journal of Health Research Africa, 2024)
Background Cerebral palsy (CP) encompasses a collection of enduring motor impairments resulting from non-progressive disruptions in the developing brain of a fetus or infant. Early detection is essential to commence prompt interventions that can greatly enhance functional outcomes and neurodevelopmental pathways. Objective To assess the efficacy of DDST II in the early identification of cerebral palsy in infants and young children at a tertiary care facility. Methods This observational study began in June 2022 at Jawaharlal Nehru Medical College & Hospital in Bhagalpur. One hundred infants and children, between 6 months to 2 years, with suspected developmental delays were assessed using the Denver Developmental Screening Test II (DDST II). Children designated as "suspect" or "untestable" received further assessment through neurological examination, neuroimaging (MRI), and follow-up consultations to validate the medical diagnosis of cerebral palsy (CP). The correlation between DDST II results and the clinical diagnosis of cerebral palsy was analyzed. Results Of the 100 children screened, 34 were categorized as "suspect" and 12 as "untestable" according to the DDST II. Out of these 46 children, 29 were ultimately diagnosed with cerebral palsy through clinical and radiological assessments. The DDST II exhibited a sensitivity of 93.5% and a positive predictive value of 63% in identifying children with cerebral palsy. Delays in gross motor and language skills characterize most cases of cerebral palsy. Children identified by DDST II received earlier therapeutic interventions than those diagnosed subsequently based solely on clinical suspicion. Conclusion DDST II serves as an efficient and practical screening instrument for the initial identification of cerebral palsy in infants and young children. Recommendation Incorporating it into standard developmental monitoring can assist in early diagnosis and timely intervention, particularly in resource-limited pediatric environments.